A CO2–Δ14CO2 inversion setup for estimating European fossil CO2 emissions - C. Gómez-Ortiz; G. Monteil; G. Monteil; S. Basu; S. Basu; M. Scholze (Atmospheric Chemistry and Physics)
Independent estimation and verification of fossil CO2 emissions on a regional and national scale are crucial for evaluating the fossil CO2 emissions and reductions reported by countries as part of their nationally determined contributions (NDCs). Top-down methods, such as the assimilation of in situ and satellite observations of different tracers (e.g., CO2, CO, Δ14CO2, XCO2), have been increasingly used for this purpose. In this paper, we use the Lund University Modular Inversion Algorithm (LUMIA) to estimate fossil CO2 emissions and natural fluxes by simultaneously inverting in situ synthetic observations of CO2 and Δ14CO2 over Europe. We evaluate the inversion system by conducting a series of observing system simulation experiments (OSSEs). We find that in regions with a dense sampling network, such as western/central Europe, adding Δ14CO2 observations in an experiment where the prior fossil CO2 and biosphere fluxes are set to zero allows LUMIA to recover the time series of both categories. This reduces the prior-to-truth root mean square error (RMSE) from 1.26 to 0.12 TgC d−1 in fossil CO2 and from 0.97 to 0.17 TgC d−1 in biosphere fluxes, reflecting the true total CO2 budget by 91 %. In a second set of experiments using realistic prior fluxes, we find that in addition to retrieving the time series of the optimized fluxes, we are able to recover the true regional fossil CO2 budget in western/central Europe by 95 % and in Germany by 97 %. In all experiments, regions with low sampling coverage, such as southern Europe and the British Isles, show poorly resolved posterior fossil CO2 emissions. Although the posterior biosphere fluxes in these regions follow the seasonal patterns of the true fluxes, a significant bias remains, making it impossible to close the total CO2 budget. We find that the prior uncertainty of fossil CO2 emissions does not significantly impact the posterior estimates, showing similar results in regions with good sampling coverage like western/central Europe and northern Europe. Finally, having a good prior estimate of the terrestrial isotopic disequilibrium is important to avoid introducing additional noise into the posterior fossil CO2 fluxes.